2021
DOI: 10.1002/edn3.251
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing an enclosed bead beating extraction method for microbial and fish environmental DNA

Abstract: DNA extraction is a critical step in processing environmental DNA (eDNA), influencing biodiversity estimates and ecosystem monitoring. Sterivex filters have become popular for collecting aquatic eDNA, allowing for on-site filtration and reduced contamination. Yet, extracting eDNA from an enclosed filter remains laborious. Recent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…More water needed to be DNA extracted from Bedok samples in order to obtain enough DNA for all experiments (Lim et al, 2016; Loh, 2019). DNA extraction utilized a conventional phenol–chloroform protocol (see Appendix S2: Materials and Methods [Sambrook & Russell, 2006]) although the literature illustrates that bead‐based and commercial kits are also suitable for the extraction of eDNA (for example, bead‐based DNA extraction: Anderson & Thompson, 2022; commercial kits: Kumar et al, 2022), and we are now also using such kits in follow‐up studies. Negative controls were included in each round of DNA extraction (“extraction negatives”, nine in total), whereby empty Falcon tubes were used in place of sample tubes.…”
Section: Methodsmentioning
confidence: 99%
“…More water needed to be DNA extracted from Bedok samples in order to obtain enough DNA for all experiments (Lim et al, 2016; Loh, 2019). DNA extraction utilized a conventional phenol–chloroform protocol (see Appendix S2: Materials and Methods [Sambrook & Russell, 2006]) although the literature illustrates that bead‐based and commercial kits are also suitable for the extraction of eDNA (for example, bead‐based DNA extraction: Anderson & Thompson, 2022; commercial kits: Kumar et al, 2022), and we are now also using such kits in follow‐up studies. Negative controls were included in each round of DNA extraction (“extraction negatives”, nine in total), whereby empty Falcon tubes were used in place of sample tubes.…”
Section: Methodsmentioning
confidence: 99%
“…In any case, most commercially available extraction kits are designed for liquid cultures or tissues that fully dissolve. This circumstance has resulted in a wide array of “standard” modifications to manufacturers’ protocols (e.g., Cruaud et al, 2017 ; Ushio, 2019 ; Anderson and Thompson, 2022 ), further complicating the quest for harmonized practice.…”
Section: Filtration Strategymentioning
confidence: 99%
“…In comparisons of three tested kits offered by Qiagen (Qiagen GmbH, Hilden, Germany), the DNeasy Blood & Tissue kit provided the best results for DNA yield ( Djurhuus et al, 2017 ; Hinlo et al, 2017 ) and equaled or outperformed the PowerWater kit in metabarcoding data quality and consistency ( Jeunen et al, 2019 ), particularly when modified with a bead-beating step ( Djurhuus et al, 2017 ). Other less commonly used kits described in the literature we reviewed ( Supplementary Table S1 ) include the ZymoBIOMICS 96 DNA/RNA MagBead (e.g., Anderson and Thompson, 2022 ), Epicentre MasterPure DNA purification (e.g., Geerts et al, 2018 ), Qiagen AllPrep DNA/RNA mini (e.g., Cruaud et al, 2017 ), and Presto Mini gDNA (e.g., Jeunen et al, 2019 ), but we found too few studies describing the performance of these kits to comment further.…”
Section: Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations